Optimalisasi Metode Pembelajaran Discovery Learning Pada Pembelajaran Sosiologi di SMA Negeri 3 Maros - Muh. Ali Fikri Subair; Rini Kurnia; Misriah Majid; Nurul Magfirah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The sociology learning process in class X IPS 2 SMAN 3 MAROS is very worrying. This is because many students play during the lesson. Therefore, teachers must ensure that students understand their lessons by using appropriate learning methods. Furthermore, research was conducted at SMAN 3 MAROS to find out how effective the discovery learning method is in teaching sociological concepts to students. Classroom action research (CAR) is a type of research in which teachers collaborate to improve class performance and student learning outcomes by thinking about, implementing, and planning what will be done. The subjects of this research were 35 students of class X IPS 2 UPT SMA Negeri 3 Maros. The implementation of P2K is carried out in 2 cycles, each cycle lasts for 1 meeting consisting of 6 teaching and learning process meetings and 2 meetings for learning results tests. The result of implementing discovery learning is that during classroom action research in cycle I and cycle II, the discovery learning model made lessons that were usually considered difficult for some students become enjoyable.